2020
DOI: 10.1101/2020.05.13.093864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyperbolic odorant mixtures as a basis for more efficient signaling between flowering plants and bees

Abstract: Animals use odors in many natural contexts, for example, for finding mates or food, or signaling danger. Analyses of natural odors search for either the most meaningful components of a natural odor mixture, or they use linear metrics to analyze the mixture compositions. Both analyses assume that the odor space itself is Euclidian, like visual and auditory spaces. However, we have recently shown that the physical space for complex mixtures is 'hyperbolic' -curved -because of the correlations that arise in biosy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…We found that the natural odor abundance data was best described by a threedimensional hyperbolic space with a negative curvature of -5.12. These results echo previous results using a more limited dataset of natural fruit or flower odor sources where hyperbolic geometry also provided a significantly better fit than the standard Euclidean geometry 12,45 . The intuitive explanation for these findings is that hyperbolic spaces provide good descriptions of the structure of natural odor spaces because they arise as continuous approximations to tree-like hierarchical networks.…”
Section: Melanogaster Is An Ecological Generalist and Human Commensalsupporting
confidence: 88%
See 3 more Smart Citations
“…We found that the natural odor abundance data was best described by a threedimensional hyperbolic space with a negative curvature of -5.12. These results echo previous results using a more limited dataset of natural fruit or flower odor sources where hyperbolic geometry also provided a significantly better fit than the standard Euclidean geometry 12,45 . The intuitive explanation for these findings is that hyperbolic spaces provide good descriptions of the structure of natural odor spaces because they arise as continuous approximations to tree-like hierarchical networks.…”
Section: Melanogaster Is An Ecological Generalist and Human Commensalsupporting
confidence: 88%
“…This space was also found to be hyperbolic, but with much smaller curvature (0.05) and higher dimensionality (dim=6). Since odor distances in the hyperbolic embedding better captured the correlational structure of abundances of odors across natural sources that stem from hierarchical odor as compared to equivalent distances computed from a Euclidean embedding 12,45 , we used hyperbolic distances as a metric of odor relationships in natural source space.…”
Section: Melanogaster Is An Ecological Generalist and Human Commensalmentioning
confidence: 99%
See 2 more Smart Citations